2001
DOI: 10.1046/j.1440-1827.2001.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1‐associated unusual pleomorphic astrocytoma displaying continual malignant progression

Abstract: Patients with neurofibromatosis type 1 (NF1) often have gliomas as a complication, most of which are benign pilocytic astrocytomas which have arisen in optic pathways. In the present case, a 17-year-old girl (at death) with stigmata of NF1, initially had a bulky tumor mass in the left thalamus, developing into the lateral ventricle, at 13 years of age. Partially resected tissue samples showed pleomorphic astrocytoma with abundant xanthoma cells and degenerative structures such as Rosenthal fibers (RF) and eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…In the latter case, the primary lesion was a solid left thalamic-lateral ventricular mass whose histomorphology was reported in part as revealing large pleomorphic and xanthomatous cells. Occasional intracytoplasmic eosinophilic granular inclusions were recognized; the tumor cells were GFAP positive, but in all, the diagnosis of PXA-NF1 did not appear to be in the authors' consideration [26]. Nevertheless, no case as far as we know of PXA-NF1 has so far been reported in an African.…”
Section: Pxa-nf1mentioning
confidence: 67%
See 1 more Smart Citation
“…In the latter case, the primary lesion was a solid left thalamic-lateral ventricular mass whose histomorphology was reported in part as revealing large pleomorphic and xanthomatous cells. Occasional intracytoplasmic eosinophilic granular inclusions were recognized; the tumor cells were GFAP positive, but in all, the diagnosis of PXA-NF1 did not appear to be in the authors' consideration [26]. Nevertheless, no case as far as we know of PXA-NF1 has so far been reported in an African.…”
Section: Pxa-nf1mentioning
confidence: 67%
“…The case reported by Saikali et al was of particular interest because it was a case of multicentric supratentorial cerebral and infratentorial cerebellar hemispheric PXA in NF1 [23]. Another case of a 13-year-old child reported by Yokoo et al in 2001 is also of interest being an example of NF1-associated unusual pleomorphic astrocytoma with malignant progression [26]. In the latter case, the primary lesion was a solid left thalamic-lateral ventricular mass whose histomorphology was reported in part as revealing large pleomorphic and xanthomatous cells.…”
Section: Pxa-nf1mentioning
confidence: 99%
“…Our case is in accordance with these observations. Studies have reported that PXA can exhibit a synchronous multicentric pattern19 or result in multiple recurrences 9. Multifocal occurrence of PXA manifesting at different time frame is extremely uncommon but has been reported 20…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed surgery is the most important therapeutic approach,1 9 18 21 if anaplastic PXA is confirmed, the active adjuvant of radio and chemotherapy may be useful. One case has been reported in which the use of neoadjuvant vincristin and carbiplatin was effective for controlling bleeding during surgery, presumably due to devascularisation 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation